A new species of pimelodus la cépède, 1803 (siluriformes: Pimelodidae) from rio ribeira de iguape basin, Brazil - Ribeiro, Frank Raynner Vasconcelos; Lucena, Carlos Alberto Santos de; Oyakawa, Osvaldo Takeshi (Neotropical Ichthyology, 2011)
Pimelodus multicratifer, a new species, is described from the rio Ribeira de Iguape basin. The new species differs from the other Pimelodus species by the following features: 26 to 30 gill rakers on the first branchial arch; a combination of three to six rows of dark spots regularly or irregularly scattered on the flanks and several small dark spots irregularly scattered on the dorsal surface of head, supraoccipital process, and sometimes on the dorsal and caudal fins; striated lips; maxillary barbels reaching between posterior tip of the pelvic-fin rays and posterior tip of the middle caudal-fin rays. © 2011 Sociedade Brasileira de Ictiologia.
Keywords: Barbus; Pimelodidae; Pimelodus; Siluriformes